Preservation of Epstein–Barr virus status and mismatch repair protein status along the metastatic course of gastric cancer. Issue 5 (21st April 2020) - Dislich, Bastian; Blaser, Nicola; Berger, Martin D; Gloor, Beat; Langer, Rupert
Abstract : Aims: Epstein–Barr virus (EBV) in‐situ hybridisation and mismatch repair (MMR) protein immunohistochemistry identifies two subgroups of gastric cancer (GC) with high immunogenicity and likelihood for response to immune check‐point inhibition. As tumour biology may change during the metastatic course, which can negatively influence the success of therapeutic decisions made on primary tissue, we investigated the consistency of GC EBV and MMR status within primary tumours and metastases. Methods and results: We investigated a cohort of 415 primary resected GC, including 111 cases with corresponding distant metastases and 297 cases with lymph node metastases. Tumours were analysed by EBV in‐situ hybridisation and MLH1, PMS2, MSH2 and MSH6 immunohistochemistry using tissue microarray technique. Primary tumours were grouped as EBV‐positive MMR‐proficient, EBV‐negative MMR‐deficient and EBV‐negative MMR‐proficient. Eleven of 415 (2.7%) of primary tumours were EBV‐positive MMR‐proficient, whereas 49 of 415 (11.8%) of tumours were EBV‐negative MMR‐deficient. EBV and MMR protein status showed full concordance with that of the primary tumours. MMR‐deficient tumours were of lower pT‐category ( P < 0.001), had fewer lymph node metastases [24 of 49 (49%) versus 273 of 361 (75.6%) cases; P < 0.001] and a lower rate of distant metastases [six of 49 (12.2%) versus 105 of 366 (28.7%) cases; P = 0.015]. Conclusion: We demonstrate a strong correlation of EBV and MMR status between primary tumours, lymph node and distant metastases in a large series of primary resected GC. The cases showed the expected frequency of EBV‐positive MMR‐deficient and EBV‐negative MMR‐proficient tumours. We conclude that tissue testing for molecular subtyping for therapeutic decision‐making can be reliably performed on primary tumours and metastases in GC.